Two Case Studies of Linguistic Variation in Mishnaic Hebrew. (17th February 2020) - Mor, Uri
Abstract: Mishnaic Hebrew shows considerable linguistic variation, which may be narrowed down to three phases: the original living language, its literary crystallization, and its written and oral transmission. While scholars of Mishnaic Hebrew are well aware of this fact, they generally do not explore it and neglect to utilize tools of variationist linguistics and historical sociolinguistics in order to enhance their understanding of the language and the motivations of its users. This paper calls for a careful integration of variationist and sociolinguistic methods into the research on Mishnaic Hebrew and offers two case studies that demonstrate the advantages of this approach. The first case study con-cerns the distribution of the two feminine singular demonstrative pronouns and, for which I argue for a variationist rather than structuralist analysis. The second case study concerns a metalinguistic discussion in tractate 'Eruvin of the Babylonian Talmud, which is claimed here to demonstrate the ideological nature of rabbinic litera-ture and its linguistic implications.